Analysis Of Passing Skills Down In The Game Volleyball - Wendy Sahputra; Supriyanto Supriyanto; Mariska Febrianti (Hanoman Journal: Physical Education and Sport, 2020)
This study aims to determine the skills of students in doing Passing Under Volleyball in Grade VI students at SD Negeri 112 Seluma Regency. The method used in this research is quantitative descriptive which is conducted to determine the value of the independent variable, either one or more (independent) variables without making comparisons or linking with other variables.The population in this study were students who sat in grade VI SD Negeri 112 Seluma. Sampling in this study using total sampling, because the entire population was sampled, amounting to 32 students. The data analysis technique used is a percentage. From the results of data analysis, description, testing of research results, and discussion, it can be concluded that the under-passing ability of Class VI students at SD Negeri 112 Seluma is at the qualification level of the ability of the "good" category of 56.25 % (18 students), the "medium" category was 34.37% (11 students), and the "poor" category was 9.38% (3 students). So that it can be concluded that most Grade VI students at SD Negeri 112 Seluma are already able to pass under well.